2008
DOI: 10.1053/j.gastro.2007.10.010
|View full text |Cite
|
Sign up to set email alerts
|

PTEN Down-Regulation by Unsaturated Fatty Acids Triggers Hepatic Steatosis via an NF-κBp65/mTOR-Dependent Mechanism

Abstract: Hepatic steatosis can be mediated by alterations of PTEN expression in hepatocytes exposed to high levels of unsaturated fatty acids. Furthermore, our data revealed interaction between mTOR and NF-kappaB, suggesting cross-talk between these 2 pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
136
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 132 publications
(152 citation statements)
references
References 31 publications
14
136
2
Order By: Relevance
“…The RNA level of HOTAIR was upregulated in all groups of cells treated with FFAs (all P < 0.05) (Figure 1(c)). And consistent with previous studies [19], PTEN mRNA and protein levels were decreased in the cells treated with 50 µM OA or LA; in addition, PA, PA/OA, or PA/OA# also resulted in down-regulation of PTEN mRNA and protein levels (all P < 0.05) (Figure 1(c,d)). …”
Section: Ffa Treatment Promotes Triglyceride Accumulation In Hepg2 Cesupporting
confidence: 91%
See 2 more Smart Citations
“…The RNA level of HOTAIR was upregulated in all groups of cells treated with FFAs (all P < 0.05) (Figure 1(c)). And consistent with previous studies [19], PTEN mRNA and protein levels were decreased in the cells treated with 50 µM OA or LA; in addition, PA, PA/OA, or PA/OA# also resulted in down-regulation of PTEN mRNA and protein levels (all P < 0.05) (Figure 1(c,d)). …”
Section: Ffa Treatment Promotes Triglyceride Accumulation In Hepg2 Cesupporting
confidence: 91%
“…It is usually down-regulated in patients and rodent models with NAFLD and HCC [13][14][15][16]. Vinciguerra et al [19,20] showed that PTEN down-regulation induced by unsaturated FFAs could accelerate triglyceride accumulation in hepatocytes, and promotes hepatoma proliferation and progression. Accordingly, the present study showed that PTEN was down-regulated in HepG2 cells exposed to FFAs, further supporting the modeling of HepG2 cells into a model of NAFLD upon treatment of PA and OA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatty acids have been reported to regulate Akt activity in a PTEN-dependent or -independent manner (34). For example, in vascular endothelial cells, palmitic acid inhibited basal Akt phosphorylation and insulin-stimulated Akt phosphorylation by increasing PTEN transcription (35).…”
Section: Discussionmentioning
confidence: 99%
“…However, adding to the complexity of PTEN function, transgenic mice, overexpressing PTEN, display increased energy expenditure and insulin sensitivity [11,12]. Regarding the liver, we previously reported that PTEN is downregulated in steatotic livers of obese patients, as well as in rat models of genetic or diet-induced obesity [13]. Likewise, PTEN is downregulated in the liver of patients infected with hepatitis C virus (HCV) [14].…”
Section: Introductionmentioning
confidence: 99%